Weegy: -3 -3
Divide each term in the inequality by 3.
(3(5x-16))/(3)>-(3)/(3)
Simplify the left-hand side of the inequality by canceling the common factors.
5x-16>-(3)/(3)
Simplify the right-hand side of the inequality by simplifying each [ term.
5x-16>-1
Since -16 does not contain the variable to solve for, move it to the right-hand side of the inequality by adding 16 to both sides.
5x>16-1
Subtract 1 from 16 to get 15.
5x>15
Divide each ... (More)

6 = 2x + 16 - 5x

3x = 16 - 6

x = 10/3 or 3 1/3

So, the solution for 6 = 2(x + 8) - 5x is B. 3 1/3